Posouzení rizik při provádění zatěžovacích zkoušek stavebních konstrukcí - Ešpandr, Jan (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2016)
Diplomová práce se zabývá analýzou rizik při provádění zatěžovacích zkoušek stavebních konstrukcí. Práce se zaměřuje na vysvětlení některých pojmů z oblasti rizikologie, popis jednotlivých typů zatěžovacích zkoušek stavebních konstrukcí, identifikaci rizik při provádění zatěžovacích zkoušek a jejich zhodnocení. Pro zhodnocení jednotlivých rizik byly použity analytické metody. Pro základní rozpoznání rizik bylo použito Ishikawových diagramů. Dále byla tato rizika podrobněji zhodnocena v analýze FMEA a výsledky zaneseny do Paretových diagramů. V závěru praktické části diplomové práce byla využita metoda HRA pro přesnější zhodnocení lidské chyby v celém procesu provádění zatěžovacích zkoušek stavebních konstrukcí.

This diploma thesis deals with the analysis of the risks during the executing of the loading tests of building constructions. The thesis focuses on the explanation of some of the terms in the field of risk management, the description of the individual types of loading tests of building constructions, the identification of the risks during the loading tests and their assessment. Analytical methods were used for assessing of the individual risks. Ishikawa diagrams were used for the basic identification of the risks. These risks were further assessed in the FMEA analysis and the results were filled in the Pareto charts. In conclusion of the practical part of the diploma thesis the HRA method was used for the more precise assessment of the human failure in the whole process of executing of the loading tests of building constructions.
Risk assessment in the implementation of load tests on building structures
Keywords: Rizikové inženýrství; zatěžovací zkoušky stavebních konstrukcí; FMEA; Paretův diagram; Ishikawův diagram; HRA; Risk Engineering; loading tests of structures; FMEA; Preto chart; Ishikawa diagram; HRA